2011
DOI: 10.3109/01902148.2010.535093
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of EPHX1, GSTP1, GSTM1, and GSTT1 genetic polymorphisms with antioxidative stress markers in chronic obstructive pulmonary disease

Abstract: This study was undertaken to ascertain if a relationship existed between oxidative status and polymorphisms of microsomal epoxide hydrolase X1 (EPHX1), glutathione S-transferase P1 (GSTP1), GSTM1, and GSTT1 in chronic obstructive pulmonary disease (COPD). Erythrocyte glutathione peroxidase (GSH-px), glutathione reductase (GR), superoxide dismutase (SOD), catalase (CAT), and plasma GST activities and total antioxidant status (TAS) as antioxidative stress markers were determined and compared either with individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…Hence it is suggested that there may be a strong association of GST with lung function at the molecular level [44][45][46][47][48]. Interestingly, in this investigation, we also found GST activity was not only lower in COPD but also progressively decreased with the severity of COPD disease.…”
Section: Discussionsupporting
confidence: 71%
“…Hence it is suggested that there may be a strong association of GST with lung function at the molecular level [44][45][46][47][48]. Interestingly, in this investigation, we also found GST activity was not only lower in COPD but also progressively decreased with the severity of COPD disease.…”
Section: Discussionsupporting
confidence: 71%
“…These results were consistent with Sahar S. Bessa et al's study in Egyptian patients with essential hypertension [29], and Lakhdar R. et al's study in the patients with chronic obstructive pulmonary disease [30]. Not as we observed in healthy young adults (in them the GST activity performing as GSTM1 genotype dependent) [31], GSTT1 deletion significantly increased the GST activity ( P  = 0.034, <0.05) in the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…He et al (11) showed the combination of GSTT1 null genotype and GSTM1 and GSTP1 risk genotypes to be related to lung function impairments, while Lakhdar et al (33) concluded that combined GSTM1, GSTT1, GSTP1 and EPHX1 genetic polymorphisms may have favourable effects on redox balance in COPD patients. Rodriguez et al (14) found the modulating role of GSTP1 in COPD to take effect only in smokers lacking AAT.…”
Section: Gstp1 Gstm1 and Gstt1 Genetic Polymorphismsmentioning
confidence: 99%